Short-term effects of simultaneous cardiovascular workout and personal music device use on the otoacoustic emissions of young adults - Soer, Maggi E. (Magdalena Elizabeth) (University of Pretoria, 2015)
Dissertation (MLOG)--University of Pretoria, 2014.